Analisis Konsumsi Daya Listrik Berpemindah Daya V-Belt dan Synchronous Belt pada Sepeda Motor Listrik Hasil Konversi - Darmono, Bambang; Kusuma, Harun Indra; Mahera, Liza (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The energy source of the converted electric motorcycle is from the battery. The type of battery used is lithium-ion with a capacity of 72 V/20 Ah. The purpose of this research is to increase the efficiency of electrical power consumption required by the driving motor from previous research, where the electrical power consumption of the converted electric motorcycle with a v-belt power transmission at a driving speed of 50 km/h is 724 Watts. It is only able to cover a distance of 99 km. The method used in this research is to test the electrical power consumption of the converted electric motorcycle with a synchronous belt power transfer. The results of the test show that the converted electric motorcycle with a synchronous belt power transfer consumes only 305 Watts of electrical power at a speed of 50 km/h. This means that the efficiency of electrical power consumption increases by 120% compared to the v-belt power transfer, and the driving distance at a speed of 50 km/h is 235 km.